2023
DOI: 10.3390/su152316153
|View full text |Cite
|
Sign up to set email alerts
|

Design and Analysis of a Peak Time Estimation Framework for Vehicle Occurrences at Solar Photovoltaic and Grid-Based Battery-Swappable Charging Stations

Fawad Azeem,
Bakhtawar Irshad,
Hasan A. Zidan
et al.

Abstract: Due to global environmental impacts, the electric vehicle (EV) adoption rate is increasing. However, unlike conventional petrol vehicles, EVs take a considerable time to charge. EVs on the road with different battery charging statuses and driving demographics may cause uncertain peak time arrivals at charging stations. Battery-swappable charging stations are a quick and easier way to replace uncharged batteries with charged ones. However, charging due to uncertain EV arrival causes higher charging profiles pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The authors of [12] constructed a real-time battery swap pricing model for ETs. The authors of [13] analyzed the impact of swapping price on the operation of BSSs, and the results showed that a reasonable swapping price can smooth the load curve and reduce system losses. In [14], a Monte Carlo simulation was used to analyze the service capability and profitability of charging stations and BSSs for taxis and buses.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of [12] constructed a real-time battery swap pricing model for ETs. The authors of [13] analyzed the impact of swapping price on the operation of BSSs, and the results showed that a reasonable swapping price can smooth the load curve and reduce system losses. In [14], a Monte Carlo simulation was used to analyze the service capability and profitability of charging stations and BSSs for taxis and buses.…”
Section: Introductionmentioning
confidence: 99%